On Upper and Lower fsgb-Continuous Multifunctions in Fuzzy Topological Spaces - Kulkarni, Megha; Karnel, Jenifer (Communications in Mathematics and Applications, 2024)
In this study, the weaker forms of fuzzy multifunctions such as upper and lower fsgb-continuous multifunctions are introduced and their properties are examined. Further, the characteristics of upper and lower fsgb-irresolute multifunctions have also been studied.